Provisional Agenda for the Twenty-Fifth Meeting of the International Monetary and Financial Committee. (Policy Papers; Policy Paper ;, 2012)
The following is the provisional agenda for the Twenty-Fifth Meeting of the International Monetary and Financial Committee, which is to be convened at the IMF's Headquarters in Washington, D.C. on April 21, 2012.